The Science Ambassador Program: partnering scientists with science teachers. - Hamner HC; Flores AL; Prue CE; Mersereau P (American Journal of Health Education)
This article focuses on the development and implementation of the Science Ambassador (SA) Program, which targets adolescents by working directly with science teachers who write and implement lesson plans that feature public health topics. The main goals of the program are to develop science lesson plans on public health topics, expose adolescents to health information at an earlier, formative age, and inspire adolescents to explore future careers in public health. The information presented in this article is intended to give other program planners insight into the structure and implementation of the program and to share valuable lessons learned.